Cadaveric Evaluation of Different Approaches for Quadratus Lumborum Blocks - Hun-Mu Yang; Sang Jun Park; Kyung Bong Yoon; Kyoungun Park; Shin Hyung Kim (Pain Research and Management)
Background. A quadratus lumborum (QL) block is an abdominal truncal block technique that primarily provides analgesia and anaesthesia to the abdominal wall. This cadaveric study was undertaken to compare the dye spread between different needle approaches for ultrasound-guided QL blocks in soft-embalmed cadavers. Methods. After randomization, an experienced anesthesiologist performed two lateral, three posterior, and five alternative QL blocks on the left or right sides of five cadavers. The target injection point for the alternative approach was the lumbar interfascial triangle, same as that of conventional posterior QL block, with a different needle trajectory. For each block, 20 ml of dye solution was injected. The lumbar region and abdominal flank were dissected. Results. Ten blocks were successfully performed. Regardless of the approach used, the middle thoracolumbar fascia was deeply stained in all blocks, but the anterior layer was less stained. The alternative approach was more associated with spread of injectate to the transversus abdominis and transversalis fascia plane. Despite accurate needle placement, all lateral QL blocks were associated with a certain amount of intramuscular or subcutaneous infiltration. Two posterior QL blocks showed a deeply stained posterior thoracolumbar fascia, and one of them was associated with obvious subcutaneous staining. The subcostal, iliohypogastric, and ilioinguinal nerves were mostly involved, but the thoracic paravertebral space and lumbar plexus were not affected in all blocks. Conclusions. The alternative approach for QL blocks was able to achieve a comparable extent when compared to the conventional approach.